Foschini Group Ltd : transforming HR - Maunder, Peta Krost (SAGE knowledge. Cases., 2016)
Foschini Group's (FOS) Shani Naidoo was in excellent spirits when she walked out of a two-day group strategy meeting in October 2009. As managing director for group human resources (HR) since 2005, it was evident that the changes that she and her team had implemented had successfully made HR a critical part of Foschini's overall business strategy. In pursuit of their vision to get rid of the company's silo mentality, the HR team had introduced a totally new, centralised HR model. Despite the shake-up, Naidoo believed there was still a great deal more that needed to change. She did wonder, however, if she might have gone too far.